The Effect of the Addition of Citrus Fruits Juice on The Physical and Chemical Characteristics of Sapodilla (Manikara zapota) Sliced Jam - Kesuma Sayuti; E P Mutiara; D Silvy (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aims to determine the effect of various citrus fruit juices on the qualities of sliced sapodilla jam. Completely randomized design (CRD) with four treatments and four replications. A (2% citric acid) served as the control, B (26% lime juice), C (26% lemon juice), and D (26% kaffir lime juice) were the treatments. The data were statistically examined using ANOVA and Duncan's New Multiple Range Test (DNMRT) at the 5% significance level. The addition of citrus fruit juice had a substantial influence on the jam's folding test, total titrated acid, pH value, water content, ash content, total dissolved solids, total sugar, crude fiber, and vitamin C did not affect its water activity. According to the chemical features, the addition of lime juice as a source of citric acid resembles the characteristics of sheet jam made with pure citric acid more closely.